(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2024)
Obtaining the greatest profit or profit with the fewest expenses is the primary objective of any business. Companies frequently ignore the effects of their operations in the workplace, such as the social and environmental repercussions that lead to interpersonal disputes. Consequently, locals frequently express their displeasure with the company’s administration through protests and rallies. With a focus on mining businesses, this study seeks to demonstrate the partial and simultaneous influence of public share ownership, debt to equity ratio, company size, and net profit margin on CSR disclosure. A quantitative technique combining a descriptive and verification methodology was employed in this study. Multiple linear regression analysis was used for the statistical testing; at a significance level of 0.05, the f-test and the t-test were used to evaluate simultaneous effects and partial effects, respectively. The findings, It has been demonstrated through statistical testing that public shareholders, debt to equity ratio and company size has significantly and favourably affects corporate social responsibility disclosure. It has been only net profit margin has little bearing on corporate social responsibility disclosure. Simultaneous, firm size, net profit margin, debt-to-equity ratio, and public shareholders affect corporate social responsibility disclosure.